Social Entrepreneurship (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The study of social entrepreneurship (SE) has grown to be very important to businesses and scholars.Social entrepreneurship is a global phenomenon that is expanding, with more than 100 million organization dedicated to fostering positive social change. Social entrepreneurs are individuals who possess innovative solutions to the most urgent social issues facing society. They are driven and committed to solving significant societal problems and offering creative solutions for significant change. However, despite their notable and influential work, they encounter many obstacles that hinder their attempts to bring about constructive change, such as financials limitations, legal and regulatory concerns etc. social entrepreneurship helps close the gap between societal requirements and financials needs. In this study, the problems and difficulties faced by Indian social entrepreneurs are highlighted. numerous recommendations have been made in the report with some case studies like Tata and Reliance.